2019
DOI: 10.1007/s11116-019-09978-6
|View full text |Cite
|
Sign up to set email alerts
|

Cycling culture and socialisation: modelling the effect of immigrant origin on cycling in Denmark and the Netherlands

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…While we expect that this finding is transferable to other cities with a distinct cycling culture, in particular cities in the Netherlands (Carstensen and Ebert, 2019;Haustein et al, 2019b;Nello-Deakin and Nikolaeva, 2020), the bike does not play a relevant role as an alternative to the car in low-cycling countries. Thus, in lowcycling countries the relation we found between complex activity patterns, perceived mobility needs and the use of individual modes, is probably restricted to car use.…”
Section: Discussionmentioning
confidence: 79%
“…While we expect that this finding is transferable to other cities with a distinct cycling culture, in particular cities in the Netherlands (Carstensen and Ebert, 2019;Haustein et al, 2019b;Nello-Deakin and Nikolaeva, 2020), the bike does not play a relevant role as an alternative to the car in low-cycling countries. Thus, in lowcycling countries the relation we found between complex activity patterns, perceived mobility needs and the use of individual modes, is probably restricted to car use.…”
Section: Discussionmentioning
confidence: 79%
“…A possible explanation of this result might be the high modal share of cycling in the native-born population and the increased use of public transport from migrants. Besides, recent European empirical studies [29], [1] showed that migrants do not cycle and drive as much as non-migrants do, which in turn does not allow them to live great distances from the transportation hubs.…”
Section: Discussionmentioning
confidence: 99%
“…Travel behaviour may be influenced by ethnic background [1], [29]. Studies from the United States indicated that cities with a higher proportion of migrants also have higher transit ridership [3].…”
Section: Migrants and Transitmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to studies focusing on newcomers in a city that indicate an adaption to existing cycling cultures, studies focusing on the general immigrant population find that immigrants to high cycling countries cycle less than natives, even after years of adaption (e.g., Welsch, Conrad and Wittowsky, 2016;Haustein, Kroesen and Mulalic, 2019). Differences may be based on differences in the social and cultural background, which needs further exploration.…”
Section: Migration As Part Of the Mobility Biographymentioning
confidence: 93%